Parental Feeding Styles and Their Association With Complementary Feeding Practices and Growth in Mexican Children - Edith Y. Kim-Herrera; Ivonne Ramírez-Silva; Guadalupe Rodríguez-Oliveros; Eduardo Ortiz-Panozo; Marcela Sánchez-Estrada; Marta Rivera-Pasquel; Rafael Pérez-Escamilla; Juan Angel Rivera-Dommarco (Frontiers Media S.A., 2021)
Background: Complementary feeding practices and corresponding parental feeding styles influence nutritional status in later stages of childhood. Findings on the association of these variables with infant growth remain inconsistent; in Mexico, a research gap exists in this area.Research Aims: (1) To characterize parental feeding styles and complementary feeding practices, and (2) to evaluate the association of parental feeding styles with complementary feeding practices and infant growth at 6 and 9 months of age.Methods: Data were collected from a prospective Mexican birth cohort. Parental feeding styles, complementary feeding practices, and anthropometric data from 263 to 234 mother-child pairs (infants of 6 and 9 months of age, respectively) were analyzed. Logistic and linear regression models were used to determine the associations between variables.Results: The predominant parental feeding style was the "responsive style" (90%). Only 43.7 and 8.1% of 6- and 9-month-old infants, had adequate complementary feeding practices, respectively. At 6 months, mothers who were responsive to satiety signals had 11% lesser possibilities (OR = 0.89, 95% CI [0.80, 0.98]) of their infant having inadequate complementary feeding practices than their counterparts and "pressuring to finish" and "pressuring to eat cereal" sub-constructs were associated with lower weight for length and body mass index Z-scores (p = 0.02).Conclusions: A high proportion of infants (>40%) did not meet international recommendations. The "pressuring" parental feeding style sub-constructs were associated with growth indicators in 6-month old infants. This emphasizes the importance of promoting parental responsiveness to infant appetite and satiety signals to achieving adequate complementary feeding practices.